How is the environmental efficiency in the process of dramatic economic development in the Chinese cities?. (March 2019) - Zhang, Yu; Shen, Liyin; Shuai, Chenyang; Bian, Jing; Zhu, Mengcheng; Tan, Yongtao; Ye, Gui
Highlights: A Super-SBM with undesirable output model is applied. The environmental efficiency of 283 Chinese cities during 2003–2016 is analyzed. The overall environmental efficiency performance across the Chinese cities is low. China has achieved significant improvement in environmental efficiency across survey period. Abstract: In the past decades, unprecedented dramatic economic development in the Chinese cities has also brought serious environmental problems. In line with this, the Chinese government has been investing great efforts and resources in addressing environmental problems. However, little previous studies have been conducted in examining whether this development is efficient from a win-win perspective balance between economic growth and environmental protection. This paper presents a comprehensive analysis on the environmental efficiency (EE) in the process of dramatic economic development in the Chinese cities. The Super-slack-based measure (Super-SBM) model is adopted to analyze the EE performance. Data used for analysis are collected from 283 sample cities in China. The research results indicate that the overall EE performance across the Chinese cities is relatively low, and the differences in EE performance among the 283 cities are significant. The top three EE performers are Shenzhen, Sanya and Erdos, and Baiyin, Xinzhou and Liupanshui are the bottom three performers. The results also suggest that the EE performance in the Eastern area, where most first-tier cities are located in, is significantly higher than that in the Central and Western areas (aggregated with fourth and fifth tier-cities). From the dynamic perspective, the results show that China has achieved significant improvement in environmental efficiency across the surveyed period of 2003–2016. The research findings provide valuable references not only for the Chinese policy-makers and practitioners to adopt measures for promoting a win-win balance between environmental protection and economic development in the Chinese context, but also for further studies on environmental efficiency in the international context.